Ductile behavior of fine-grained, carbon-bonded materials at elevated temperatures. (October 2017) - Solarek, J.; Himcinschi, C.; Klemm, Y.; Aneziris, C.G.; Biermann, H.
Abstract: Carbon-bonded materials are widely used in refractory applications because of their unique chemical, physical, and mechanical properties at high temperatures. The mechanisms of their high-temperature deformation are, however, unclear. The present study reveals new results from mechanical testing of both fine-grained, carbon-bonded alumina and graphite (ISEM 8) observed at temperatures of up to 1500 °C in an inert atmosphere. The results were achieved by means of microstructural investigations by scanning electron microscopy. For Al2 O3 -C, a pronounced maximum strength vs. testing temperature occurred at 1300–1400 °C, with a change from brittle to ductile behavior. In contrast, graphite showed an increase in strength until 1500 °C and no evidence of ductile deformation. A model based on the differences in the coefficients of thermal expansion of the components is presented to explain this phenomenon. In addition, Raman spectroscopy revealed the formation of graphitic structures due to testing at 1500 °C. Graphical abstract: